A New Method to Identify Incomplete Frame of Discernment in Evidence Theory - Renliang Sun; Yong Deng (IEEE Access, 2019)
One assumption of Dempster-Shafer evidence theory (D-S theory) is the closed world. However, how to determine whether the frame of discernment is incomplete or not is still an open issue. In this paper, a new method is proposed based on a minimum spanning tree. For each new sample collected in the system, the mass function of the empty set is determined based on the proposed method. The value of the mass function of the empty set is used to determine whether the frame of discernment is incomplete or not. The experimental results on several benchmark datasets illustrate that the proposed method has a high accuracy in identifying the incomplete frame of discernment while the error rate is low.